Effects of Microhydrin® supplementation on endurance performance and metabolism in well-trained cyclists - Glazier, L. R.; Stellingwerff, T.; Spriet, L. L. (International Journal of Sport Nutrition and Exercise Metabolism, 2004)
This study investigated whether the supplement Microhydrin® (MH) contains silica hydride bonds (Si-H) and if Microhydrin supplementation increased performance or altered metabolism compared to placebo (PL) during prolonged endurance cycling. Seven endurance-trained male cyclists consumed 9.6 g of MH or PL over 48 h in a randomized, double-blind, crossover design. Subjects cycled at ~ 70% of their VO2peak coupled with five 2-min bursts at 85% VO2peak to simulate hill climbs over 2 h. Subjects then completed a time trial, which required them to complete 7 kJ/kg body mass as quickly as possible. Infrared spectrometry analysis showed a complete absence of Si-H bonds in MH. There was no difference in time trial performance between the 2 trials (PL: 2257 ± 120 s vs. MH: 2345 ± 152 s). Measured oxygen uptake, respiratory exchange ratio, carbohydrate (MH: 2.99 ± 0.13 g/min; PL: 2.83 ± 0.17 g/min avg. over 2 h) and fat (MH: 0.341 ± 0.06 g/min; PL: 0.361 ± 0.07 g/min) oxidation rates and all blood parameters (lactate, glucose, and free fatty acids) were all unaffected by MH supplementation. The volume of expired CO2 and ventilation were significantly greater with MH supplementation (P £ 0.05). The results indicate that oral Microhydrin supplementation does not enhance cycling time trial performance or alter metabolism during prolonged submaximal exercise in endurance-trained cyclists.